(untitled) (Pragyaratna प्रज्ञारत्न, 2023)
This study explores the strategies for teaching and learning science at secondary-level public schools in Nepal. A descriptive quantitative research design was adopted and non-random convenient sampling techniques were adopted in this study. An observation form and a closed-ended survey questionnaire were used for the data collection. It was found that the majority of science teachers used lecture and demonstration methods and 55% of teacher select the teaching methods on the basis of the subject matters rather than the student’s interest and classroom environment. Only 2 schools out of 11 were conduct science exhibition program and students enjoyed to participation science exhibition. Also, students used internet websites and applications including YouTube, and Facebook for learning. It is recommended that the use of student-centered approaches while teaching and learning science at secondary public schools in Nepal will have positive impact.